Circulating transforming growth factor-beta1 and progression of the mitral valve prolapse: fifteen-year follow-up. (14th October 2021) - Malev, E; Reeva, S; Timofeev, E; Zemtsovsky, E
Abstract: Introduction: Transforming growth factor-β1 (TGF-β1) is a crucial regulatory cytokine that contributes to the development of the mitral valve and regulates extracellular matrix protein synthesis in syndromic and non-syndromic mitral valve prolapse (MVP). Our aim was to evaluate the effect of elevated circulating TGF-β level on the progression of the valve myxomatosis and leaflets billowing at long-term follow-up. Methods: 78 asymptomatic young subjects (mean age 19.7±1.6, 72% male) with MVP were consecutively enrolled in our observational, prospective, single-center study. MVP was diagnosed by billowing one or both mitral leaflets >2 mm above the mitral annulus in the long-axis parasternal view. Concentration of TGF-β1 in serum was determined by enzyme-linked immunosorbent assay using a test system Human Platinum ELISA. Results: During 1170 person-years of follow-up (median 14.5 years), no deaths or MVP-related events occurred. Posterior leaflet's thickening (from 3.9±1.4 mm to 4.4±1.7 mm (D=+0.5 mm), p<0.01) and increase of the billowing (progression in maximal prolapse depth from 3.5±2.4 mm to 4.8±2.8 mm (D=+1.3 mm), p<0.001) leads to the mitral regurgitation (MR) progression (vena contracta: 2.3±0.4 mm vs. 3.5±0.4 mm (D=+1.2 mm), p<0.0001) over 15 years of follow-up. TGF-β1 serum level was increased (15.2±12.3 ng/ml) and strongly correlated with the thickening of the posterior leaflet (r=0.72; p≤0.0001). In multivariate Cox analysis the TGF-β1 level was the independent predictor of the posterior leaflet's thickening (2.07; 95% CI: 1.34 – 3.29; p=0.001) and progression of the billowing (2.89; 95% CI: 1.61 – 4.37; p=0.0001). TGF-β1 >7.0 ng/ml was a strong predictor (area under ROC curve = 0.84 (95% CI, 0.7–0.9); sensitivity 82%, specificity 95%) for progression of MVP (maximal prolapse depth increase: D +1.9±1.2 mm (TGF-β1 >7.0 ng/ml) vs. 0.7±0.6 mm (TGF-β1 <7.0 ng/ml), p<0.0001) and MR (vena contracta increase: D +1.1±0.5 mm (TGF-β1 >7.0 ng/ml) vs. 0.5±0.4 mm (TGF-β1 <7.0 ng/ml), p<0.0001). Conclusions: Despite the overall benign prognosis, we found the obvious echocardiographic progression of the valve myxomatosis and leaflets billowing at long-term follow-up in young person. Elevated above 7.0 ng/ml TGF-β1 serum level might serve as a prognostic biomarker and identifies patients with increased risk of the mitral valve prolapse progression. Funding Acknowledgement: Type of funding sources: None.